Factors Leading to Early Embryonic Death - Shah, B. R. (Nepalese Veterinary Journal, 2019)
Early embryonic death is defined as the loss of embryo or conceptus which occurs between fertilization and 15 days post insemination. Early embryonic death leads to reproductive failure in animals resulting in reduced pregnancy rates, slower genetic improvement and substantial impact on farm profitability. Early embryonic death is an eloquent limiting factor for the completion of pregnancy in animals (Inskeep and Dailey, 2005). Incidence of embryonic losses is usually higher than perinatal losses. Notably, fetal development may or may not have affected by maternal infections during pregnancy (Givens and Marley, 2008). Early embryonic death occurs before the fetal calcification. Complete resorption of the embryo is usually seen during early embryonic death (Wrathall, 1975). Embryonic or fetal death leads to resorption, mummification, maceration or abortion. Gestational age, cause of death, and source of progesterone for pregnancy maintenance are the factors that impacts the outcome of the embryonic or fetal death (Givens and Marley, 2008). Most often, early embryonic death, post implantation is due to the uterine environment rather than fetal development (Clark et al., 1986). Dead embryos, between the time of implantation and calcification, are also resorbed. If the entire litter is lost, the dam will return to service at an irregular interval, usually 5 to 10 days post pregnancy loss (Wrathall, 1975) and pregnancy is continued if even a single number of embryo remains (Christianson, 1992). In a farm or within a particular litter, more than one type of embryo or fetal death can be found, but accurate classification is important for further better investigation (Christianson, 1992). Diagnosis is usually very difficult; as the agent or cause of embryonic death is no longer present while investigation is taking place. So, it is important to be aware of variety of causes of embryonic death that helps to rule out the particular problems that can be diagnosed and treated (Christianson, 1992). Proper history such as vaccination status, feed changes, housing, environmental temperature and so forth should be taken, that helps to narrow down the potential list of problems to consider and root cause can be found.